PERSEPSI SISWA TERHADAP PENGGUNAAN LAGU-LAGU INGGRIS DALAM PENGAJARAN PELAFALAN BAHASA INGGRIS - Trisnawati, Lisa Ega; Huda, Moh. Choirul (Yayasan Amanah Nur Aman, 2025)
English songs can be a fun and effective medium for learning English pronunciation. This study aims to explore students' perceptions of the use of English songs in learning pronunciation at SMK Negeri 1 Bandung, specifically in the extracurricular English Club for the 2024/2025 academic year. This study used a descriptive qualitative method involving questionnaires and interviews with 10 students as participants. The results of the questionnaires and interviews showed that most of the students 8 out of 10 had positive perceptions. Students stated that songs made learning pronunciation more fun, easy to remember, and increased confidence in speaking. However, 2 students preferred other methods such as movies or live teacher practice. Overall, however, it can be concluded that English songs in pronunciation learning are still seen as a motivating and helpful medium in pronunciation learning.